Análisis de mecanismos de Autenticación, Autorización y Contabilización para mejorar la seguridad en entornos empresariales - Pazmiño Muñoz, María Rosa (2023)
This research carried out seeks to analyze the mechanisms of the AAA protocols, which correspond to the acrostic in the English language Authentication (authentication), Authorization (authorization) and Accounting (accounting), these processes in business fields deploy distributed security systems that provide greater security in areas of networks and network services against unauthorized access. This helps to give greater guarantee in the control of the users who connect to said network and thus, over time, have a better audit of the activities carried out by the users who have entered the network. The AAA mechanisms were designed to solve these types of problems, since in many companies they did not have control over user access to assets connected to the network and unauthorized users had easy access. According to the systematic review that was carried out, it was possible to know the channels that are most required, allowing solutions to the vulnerabilities that can occur within business environments.